A new field dependent mobility model for high frequency channel thermal noise of deep submicron RFCMOS - Ong, Shih Ni (2013)
In this paper, a new field dependent effective mobility model including the drain-induced vertical field effect (DIVF) is presented to calculate the channel thermal noise of short channel MOSFETs operating at high frequencies. Based on the new channel thermal noise model, the simulated channel thermal noise spectral densities have been compared to the channel thermal noise directly extracted from noise measurements on devices fabricated using GLOBALFOUNDRIES’ 0.13 μm RFCMOS technology. The comparison has been done across different channel length, finger width and number of finger for different frequencies, gate biases and drain biases. Excellent agreement between simulated and extracted noise data has shown that the proposed model is scalable over different dimensions and operating conditions. The proposed model is simple and can be easily implemented in a circuit simulation environment.